Transition metal-free direct dehydrogenative arylation of activated C(sp3)–H bonds: synthetic ambit and DFT reactivity predictions. Issue 41 (3rd September 2018) - Lovato, Kaitlyn; Guo, Lirong; Xu, Qing-Long; Liu, Fengting; Yousufuddin, Muhammed; Ess, Daniel H.; Kürti, László; Gao, Hongyin
Abstract : A direct and general mono-arylation of activated C(sp 3 )–H bonds with nitroarenes under transition metal-free conditions has been developed. Abstract : A transition metal-free dehydrogenative method for the direct mono-arylation of a wide range of activated C(sp 3 )–H bonds has been developed. This operationally simple and environmentally friendly aerobic arylation uses tert -BuOK as the base and nitroarenes as electrophiles to prepare up to gram quantities of structurally diverse sets (>60 examples) of α-arylated esters, amides, nitriles, sulfones and triaryl methanes. DFT calculations provided a predictive model, which states that substrates containing a C(sp 3 )–H bond with a sufficiently low p K a value should readily undergo arylation. The DFT prediction was confirmed through experimental testing of nearly a dozen substrates containing activated C(sp 3 )–H bonds. This arylation method was also used in a one-pot protocol to synthesize over twenty compounds containing all-carbon quaternary centers.